Analisis Faktor yang Mempengaruhi Pemberian Imunisasi HB-0 pada Bayi Baru Lahir - Yussi Kartika; Lensi Natalia Tambunan; Rizki Muji Lestari (Jurnal Surya Medika (JSM), 2022)
HB-0 immunization given to infants before or after contact can protect infants from hepatitis infection. The low coverage of HB-0 immunization given for less than seven days to infants is caused by some people not knowing the benefits of HB-0 immunization should be given immediately after birth. The occupation and age factors influence immunization status. To analyze the factors that influence the administration of HB-0 immunization in newborns based on the data through the literature review method—using the literature review method. Journal searches use an academic database, namely Google Scholar, published in 2017-2020 using Indonesian and English. Cross-sectional study design. They obtained six research results according to the inclusion criteria. The research sample is an average of 40-109 respondents. The research analysis results showed six research journals that there was a relationship between the factors that influenced the administration of HB-0 immunization in newborns with a value (α = 0.05). There is a relationship between knowledge, family support, occupation, age, education, and motivation in the factors influencing the administration of HB-0 immunization in newborns.